Functional analysis of read-through transcription in Saccharomyces cerevisiae - Prescott, E (2002)
The molecular consequences of read-through transcription in Saccharomyces cerevisiae genes transcribed by RNA Polymerases I and II (Pol I and Pol II) are investigated in the two results sections of this thesis (Part I and Part II). In these studies, nascent and steady state RNA analyses are employed to evaluate transcriptional termination. Part I focuses on the impact that co-expressed Pol II transcribed genes can have on each other when placed in a convergent orientation. Transcriptional interference (TI), previously shown to occur between tandemly arranged genes, inhibits initiation of transcription on a downstream gene. These studies demonstrate that TI can also occur with S.cerevisiae Pol II genes arranged convergently. When the GAL10 and GAL7 genes are rearranged in a convergent orientation, transcriptional initiation occurs at full levels. However as soon as the two transcripts begin to overlap, elongation is restricted resulting in a severe reduction in steady state mRNA accumulation. This effect is only observed in the cis arrangement arguing against RNAi effects acting on the potential generation of antisense transcripts. These data reinforce the necessity to separate adjacent Pol II transcription units by efficient termination signals. Part II describes experiments that define the nascent termination site of Pol I transcribed rRNA genes. Furthermore, transcription run-on (TRO) analysis was performed on yeast strains in which specific factors involved in the Pol I transcription and RNA processing had been deleted. In particular, S.cerevisiae strains lacking the RPA12p subunit of Pol I have a severe defect in transcriptional termination at the nascent level indicating a direct role for this subunit in termination. Additionally, a yeast strain lacking Rnt1p, a protein involved in early rRNA processing, shows an altered transcriptional termination profile suggesting a link between processing and termination efficiency. In contrast to TI in Pol II, read-through transcription in Pol I may not significantly reduce rRNA gene synthesis.